Agency and structure in a sociotechnical transition: Hydrogen fuel cells, conjunctural knowledge and structuration in Europe. (March 2018) - Upham, Paul; Dütschke, Elisabeth; Schneider, Uta; Oltra, Christian; Sala, Roser; Lores, Monica; Klapper, Rita; Bögel, Paula
Highlights: 'Strong structuration' supports the juxtaposition of psychological and sociological accounts in a single framework. The approach can be applied to give an extended account of agency in sociotechnical processes. Innovation system actor opinions are influenced by situated, conjunctural knowledge and experience. The study draws on 145 interviews with hydrogen fuel cell stakeholders in five EU countries. Abstract: Despite each level of the multilevel perspective of sociotechnical transitions reflecting a different degree of structuration, structuration perspectives have been little used to help explain sociotechnical change and stasis. Here we show how 'strong structuration' can be used to theorise the role of agency in sociotechnical systems in a way that brings together psychological and sociological perspectives. Strong structuration gives weight not only to actors' practices, but also to their experiences. Practices and structures are viewed as mutually influencing, as in Giddens' original conception, but the role of situated, subjective experience is also explicitly acknowledged. Applying this perspective, we show how individual attitudes and beliefs in relation to a niche energy technology are influenced by experience of national economic and innovation policy environments, with in turn implications for expectations of action by self and others. The overall aim is to illustrate a framework that connects individual psychology to practice, with implications for sociotechnical structure. For this purpose we draw on case study data of European R&D stakeholder opinion of stationary hydrogen fuel cell applications for heat and power, focusing particularly on the contrasting situations of the UK, Germany and Spain.